The Evaluation of Sustainable Capacity Building for Decentralization (SCBD) Project in Banjarnegara Regency - Widjonarko, Widjonarko; Sunaryo, Broto (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
The Sustainable Capacity Building for Decentralization (SCBD) project funded by the Asian Development Bank (ADB) aimed to strengthen the capacity of local governments in Indonesia. Banjarnegara Regency was selected by the ministry of internal affairs for the implementation of the project. The SCBD Project in Banjarnegara consists of five components including framework of capacity building, institutional capacity building, human resources management, human resources development and sustainable financial and budgeting. This project will is held in five years using two funding schemes phases, donor funded the first 3 years (2009â€2011), then continued by the local government of Banjarnegara. During the 2009â€2011period, the project has finished all five components, PMU then conducted evaluation to ensure achievement of the SCBDâ€™s main goal: strengthening local governance for delivering good public services. The expost evaluation method used to evaluate the SCBD Project for short term outcomes found that the project hasnâ€™t directly improved the public services performance even having completed all five components of the project. Most people in Banjarnegara Regency felt no significant improvement of public services provided by the government. The ineffectiveness of public services can be understood, because not all of the components of the SCBD project had been thoroughly implemented at local government level. Moreover, many activities of the project tend to overlap implying lack of coordination among the project implementation units.